An interesting case of Phocomelia - Lavanya, C.; Devi, T. Ramani; Gayathri, D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Authors present a very rare case of tetra-phocomelia evaluated by antenatal ultrasonography. It is a condition seen in 0.62 per 100,000 live births. This is a congenital chromosomal abnormality involving the musculoskeletal system. Primi gravida with spontaneous conception after a long period of infertility underwent early anomaly scan. Patient was not aware of the last menstrual period hence; NT scan was missed. Routine early anomaly scan done between 16-18 weeks of pregnancy diagnosed a fetus with Tetra-Phocomelia. Due to the lack of associated symptoms or significant history, our case did not fit into any specific syndrome and appears to be the result of a sporadic, non-hereditary limb deficiency involving all four limb buds. Second opinion obtained from a fetal medicine consultant who confirmed the diagnosis. Hence, decided for mid trimester termination and fetus was expelled after 8 hours. Fetus was not sent for pathological analysis. Tetra-phocomelia is a rare congenital anomaly and it may be associated with other deformity also. 1st case of phocomelia was described after the intake of thalidomide. In this condition hands and feet are seen as small flippers of a seal. The differential diagnosis includes sporadic phocomelia, Holt-Oram syndrome, thrombocytopenia-absent radius syndrome (TAR syndrome), Robert’s syndrome, and thalidomide-induced phocomelia. Here authors are presenting a rare case of Phocomelia where there is no history of drug intake or family history. This has to differentiate from thrombocytopenia-absent radius syndrome (TAR syndrome), sporadic phocomelia, Holt-Oram syndrome, Robert’s syndrome, and thalidomide-induced phocomelia.